Systematic Review of Primary Immunodeficiency Diseases in Malaysia: 1979–2020 - Abd Hamid, Intan Juliana; Azman, Nur Adila; Gennery, Andrew R.; Mangantig, Ernest; Hashim, Ilie Fadzilah; Zainudeen, Zarina Thasneem (Frontiers in Immunology, 2020)
Introduction: Primary immunodeficiency diseases (PIDs) are under-reported in Malaysia. The actual disease frequency of PID in this country is unknown due to the absence of a national patient registry for PID. Objective: This systematic review aimed to determine the prevalence rates of PID cases diagnosed and published in Malaysia from 1st of January 1979 until 1st of March 2020. It also aimed to describe the various types of PIDs reported in Malaysia. Method: Following the development of a comprehensive search strategy, all published literature of PID cases from Malaysia was identified and collated. All cases that fulfilled the International Union of Immunological Societies (IUIS) classification diagnosis were included in the systematic review. Data were retrieved and collated into a proforma. Results: A total of 4838 articles were identified and screened, with 34 publications and 119 patients fulfilling the criteria and being included in the systematic review. The prevalence rate was 0.37 per 100,000 population. In accordance with the IUIS, the distribution of diagnostic classifications was immunodeficiencies affecting cellular and humoral immunities (36 patients, 30.3%), combined immunodeficiencies with associated or syndromic features (21 patients, 17.6%), predominant antibody deficiencies (24 patients, 20.2%), diseases of immune dysregulation (13 patients, 10.9%), congenital defects in phagocyte number or function (20 patients, 16.8%), defects in intrinsic and innate immunity (4 patients, 3.4%) and autoinflammatory disorders (1 patient, 0.8%). Parental consanguinity was 2.5%. Thirteen different gene mutations were available in 21.8% of the cases. Conclusion: PIDs are underdiagnosed and under-reported in Malaysia. Developing PID healthcare and a national patient registry is much needed to enhance the outcome of PID patient care.